Personal Learning Environments (PLE) in the Bachelor’s Degree in Elementary Education at the University of Granada - Chaves-Barboza, Eduardo (2018)
This paper studies the devices that university students in teacher education incorporate into their personal learning environments (PLE). It also examines the time that students dedicate to activities related to ICT, the factors that encourage or frustrate the incorporation of tools to students’ PLE, and the characteristics that this population desires for a PLE. For this, a questionnaire has been applied using Likert scales in a sample of 668 students divided into 15 groups, enrolled in the Elementary Education Bachelor’s degree program, at the University of Granada, Spain. The data were analyzed using descriptive and inferential statistics (with 95% confidence interval). Also, correlation tests (Kendall coefficient τ) and analysis of variance (test of Kruskal-Wallis H) were employed. The results showed that laptops and smartphones are the most accessible devices for students. The findings also showed that students spend little time to visiting university platforms, they prefer PLE tools to be productive and to allow them to connect with others, and they want PLE to be interactive, customizable and useful.